Estudo químico do fungo Colletotrichum acutatum e sua interação com Citrus sinensis - Gomes, Wesley Faria (2014)
Brazil remains the world's largest orange producer, accounting for 32% of the total production of oranges and 50% orange juice. The State of São Paulo holds 97% of Brazilian exports of orange juice, possessing one of the largest citrus producing areas of the world. Citrus plants can be affected by various pathogenic agents which highlights the fungus Colletotrichum acutatum, causal agent of citrus post-bloom fruit dropwhich under certain environmental conditions, is in a limiting factor in many citrus production areas. Given the above and seen the importance of disease in the cultivation of citrus, realizes the need for information related to the chemical study of C. acutatum. Thus, this study presents the chemical study of fungal plant pathogen, in addition, discusses the study of plant-microbe interactions, identifying volatiles by HS-SPME-GC-MS as well as characteristic signals compounds produced by plants when infected. Chemical studies of C. acutatum to the isolation of certain diketopiperazines, phenolic compounds, steroids, nucleosides and glycerides. In order to encourage the production of metabolites by the fungus and understand more your metabolism, some modulators (chemical and epigenetic) were used, in addition to the growth of microorganisms in mixed cultures, where it was possible to isolate some metabolites such as 2,5-dihidroximetilfurano and IAA. Aiming to observe the behavior of the flowers as the production of metabolites when infected, the study of plant-fungus interaction, where the pathogen was inoculated in flowers of Citrus sinensis, and these were collected at 2, 4 and 7 days. The volatile components of infected flowers were identified by HS-SPME-GC-MS and compared with the healthy flowers. A methodology for biological assays as mycelial growth, spore germination and appressorium formation was implemented.